« Dans le goût de l’antique » - Arianna Esposito; Lionel Markus; Sophie Montel (In Situ)
Our interest in the history and the pedagogical collection of the Universities of Besançon and Dijon has recently led us to undertake a research program on the educational heritage linked to the teaching of art history and archaeology our region Burgundy – Franche-Comté (see here: https://ista.univ-fcomte.fr/projet-scientifique/projet-moulages). With the study of argentic photographs distributed by Parisian houses (such as Giraudon), photographic plates, works of specialized literature acquired by our libraries and collections of plaster casts assembled at the end of the 19th century, we put in relation the collections of the art schools of Dijon and Besançon. The latter, founded in the 18th century, still possesses a large collection of plasters, mainly of Graeco-Roman sculpture, which we study in the context of this paper; the municipal archives of Besançon keep an important collection which will allow us to retrace their history and customs, from the dispatches of the Ministry of Public Instruction until the school was moved in 1972. In parallel, we study the Dijon Art School collection, which deposited a large part of its collection of plaster casts at the Musée de Montbard in the 1990s; a reasoned inventory, in progress, is a first step in this research. Our contribution to this issue will first tackle certain historical aspects of the presence of these plaster collections in Burgundy – Franche-Comté in order to consider the modalities of their preservation in 2020.